2016
DOI: 10.1039/c6fo00589f
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of fish oil on pre-diabetes: a lipidomic analysis of liver ceramides in rats

Abstract: A high intake of fat and sucrose can dramatically increase bioactive lipids such as ceramides in tissues. Ceramides regulate several steps in the insulin signal pathway. The effects of n-3 PUFA on insulin resistance are inconsistent, especially in liver. We investigated the effect of n-3 PUFA (EPA/DHA 1 : 1) from fish oil on hepatic ceramides in a pre-diabetic animal model. Three groups of rats were fed standard feed, high fat high sucrose feed (HFHS) or HFHS enriched with n-3 PUFA. We investigated by lipidomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 30 publications
5
25
0
Order By: Relevance
“…FOM and FOM&GSE groups showed lower level of CSAD, involved in taurine biosynthesis from cysteine , which could indicate that glutathione synthesis was favoured in rats fed FOM diet rather than taurine synthesis, since cysteine is the limiting amino acid for both biosynthetic processes [52]. Accordingly, FOM groups tended to increase glutathione reduced levels [30]. Meanwhile, GSE diet down-regulated GLS2.…”
Section: Effect Of Fish Oils and Polyphenols On Protein And Amino Acimentioning
confidence: 94%
See 2 more Smart Citations
“…FOM and FOM&GSE groups showed lower level of CSAD, involved in taurine biosynthesis from cysteine , which could indicate that glutathione synthesis was favoured in rats fed FOM diet rather than taurine synthesis, since cysteine is the limiting amino acid for both biosynthetic processes [52]. Accordingly, FOM groups tended to increase glutathione reduced levels [30]. Meanwhile, GSE diet down-regulated GLS2.…”
Section: Effect Of Fish Oils and Polyphenols On Protein And Amino Acimentioning
confidence: 94%
“…Adiposity index: ((total abdominal fat × 100)/body weight) and hepatosomatic index: ((liver weight × 100)/body weight) were also calculated. Plasma triglycerides, total cholesterol and insulin concentrations joint to the percentage of glycated hemoglobin (HbA1c) in blood were measured in the same animals by following protocols previously described [27][28][29] and the results are currently published [30,31] . In order to facilitate the reading of the present work, a summary of those are showed in the Supplementary Tables S1 and S2, which also provide the rest of biochemical measurements done.…”
Section: Biochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters have already been studied in the same cohort of animals and partially published [15,22,23]. Rats fed the HFHS control diet developed a prediabetic state characterized by hyperinsulinemia and excess of visceral fat [13,19]. Results indicated that none of the supplementations influenced weight increase as well as adiposity and hepatosomatic indexes.…”
Section: Effects Of Fish Oil Mixture (Fom) and Grape Seed Polyphenolsmentioning
confidence: 99%
“…In adults, medium-and long-chain ceramides were found to enhance insulin sensitivity and 14 improve glucose homeostasis [70,71]. Such an impact has not been yet explored in infants.…”
mentioning
confidence: 99%